Implementation Online Reading Strategy on English Reading Comprehension Skills - Nurul Lailatul Khusniyah (ELITE JOURNAL, 2019)
The purpose of this study was to find out the implementation online reading strategy on English reading comprehension learning. This strategy gave the different ways to student in understanding of the text. Because each student has been influenced by many factors in English reading comprehension learning. This study used exploratory qualitative case study. It investigated the students’ English reading comprehension skills using online reading strategy that had used both of at school and home. The technique of collecting data used interview, observation, assignment of reading report, and test. The validity of data used credibility, transferability, dependability, and conformability. The result of study found that online reading strategy gave a positive impact on students’ pattern in English reading comprehension learning both of school and home. They had a different context and collaboration in reading learning. Online reading strategy is be appropriate media to support English reading comprehension learning using internet facilitate, for example using World Wide Web. Online reading strategies improve students' understanding of the text because the reading process is done at any time through online texts that are accessed at any time.